Perioceutics-A review - Charul Preet Kaur; Vikas Jindal; Ranjan Malhotra; Divya Jaggi; Amit Goel; Rupinder Kaur (Indian Journal of Dental Sciences, 2017)
Perioceutics or use of the pharmacological agents specifically developed to manage periodontitis is an interesting and emerging aids in the development of periodontal disease along with the mechanical debridement. The purpose of host modulatory agent which is a imperative part of perioceutic, is to restore balance between, on the one hand, pro inflammatory mediators and destructive enzymes, and on the other hand, anti-inflammatory mediators and enzyme. Host modulatory therapy (HMT) is a treatment concept that aims to reduce tissue destruction and stabilize or even regenerate the periodontium by modifying or down regulating destructive aspects of the host response and up regulating protective or regenerative responses. This paper review the Host Modulatory Therapy which in future will be the effective tool dental practitioners when used as adjunct to mechanical therapy in treating periodontal diseases.